Effective judicial protection and damages in EU law: the case for the deterrent effect - Weingerl, P (2017)
The aim of the thesis is to examine whether the prohibition of overcompensation in the Antitrust Damages Directive is compatible with the EU legal and normative framework. To this end, the analysis is carried out on two levels. First, the rationale for damages in the selected jurisdictions (England, France and Germany) and in the EU is examined to test the main underpinning justification for the prohibition of overcompensation in the Antitrust Damages Directive, i.e. the “European legal tradition argument”. Second, the thesis addresses broader constitutional implications that underpin the debate on the desirability of the pursuit to prohibit overcompensation in the EU. These entail questions pertaining to the adoption of such measures and, thus, exploring whether the EU has the legitimacy to legislate and the related question of competence and the choice of the appropriate legal basis. The argument to be advanced in this thesis is that the aim of achieving a sufficient level of deterrence with awarding damages for EU competition law infringements stems from the very conceptual basis in which the right to damages is grounded – the principle of effective judicial protection and the principle of effectiveness. Thus, as the analysis reveals, the prohibition of overcompensation is inconsistent with the EU legal framework, since it has potential to jeopardise the deterrent or dissuasive function of antitrust damages actions. The prohibition of overcompensation has significantly contributed to the business- biased gist of the Directive, and thus to breaking the link between the rationale for the right to damages for EU competition law infringements, the legal basis and the content of the Directive. The thesis ultimately argues that the Directive’s prohibition is incompatible with the principles of conferral, subsidiarity and proportionality, and to a considerable extent inconsistent with the EU’s legal and normative framework.